Analisis Hasil Resolusi Citra Dengan Metode Interpolasi Nearest Neighbor, Interpolasi Bilinear, dan Interpolasi Bicubic - Triana Elizabeth; Tinaliah tinaliah (JuSiTik : Jurnal Sistem dan Teknologi Informasi Komunikasi, 2018)
With the lightning speed of camera technology evolution, now camera can take pictures by zooming up to many times without reducing the quality of the photo. The quality of the resulting image is very dependent on the interpolation method used. This study discusses the influence of nearest neighbor interpolation methods, bilinear interpolation and bicubic interpolation with various levels of resolution on the original image. The data used in this study is 256x256 pixel RGB image. The quality of the resulting image will be measured using the MSE and PSNR. The MSE assessment results using the Bicubic Interpolation method are in the range 0-1 The results of the PSNR assessment using the Bicubic Interpolation method produced a number above 51dB. Based on the results of the study it can be concluded that resolution image quality is strongly influenced by the interpolation method used. The results of the assessment using MSE and PSNR indicate that the Bicubic Interpolation Method is better than the Bilinear Interpolation method and Nearest Neighbor Interpolation.